Understanding and Litera Legis of Marriage Law in the Milenial Era for School Children - Pujiono, Pujiono; Hidayat, Arif; Sulistianingsih, Dewi (Indonesian Journal of Advocacy and Legal Services, 2021)
In Indonesia, the marriage law is regulated in UU No. 1 of 1974 which has been amended to become UU No. 16 of 2019. In addition, non-Moslems may comply with the provisions of the marriage law contained in the Civil Code. Marriage is an initial process for the formation of family life and the beginning of the manifestation of forms of human life. The daily life of men and women, created by God Almighty, naturally haa an attraction to one another to share affection in realizing a life together or it can be said that they want to form physical and mental bonds to create a happy, harmonious, and eternal family. Understanding the marriage law needs to be done with humanist efforts and cannot be done instantly. The efforts to understand the marriage law need to be made to all levels of society, especially for school children so that the marriage they live in can be in accordance with the objectives of the marriage. School children are classified as immature and they still have an important responsibility to study. They really need information about the marriage law in order to gain a comprehensive understanding of marriage because they are in a stage of growth that is full of curiosity. This program aims that school children will not get missed-information about the marriage law. Therefore, school students are one of the targets of this program.